2011
DOI: 10.1152/ajpregu.00220.2010
|View full text |Cite
|
Sign up to set email alerts
|

Ventrolateral medulla mechanisms involved in cardiorespiratory responses to central chemoreceptor activation in rats

Abstract: A rise in arterial Pco(2) stimulates breathing and sympathetic activity to the heart and blood vessels. In the present study, we investigated the involvement of the retrotrapezoid nucleus (RTN) and glutamatergic mechanisms in the Bötzinger/C1 region (Bötz/C1) in these responses. Splanchnic sympathetic nerve discharge (sSND) and phrenic nerve discharge (PND) were recorded in urethane-anesthetized, sino-aortic-denervated, vagotomized, and artificially ventilated rats subjected to hypercapnia (end-expiratory CO(2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 43 publications
2
47
1
3
Order By: Relevance
“…The results suggest that central chemoreceptor-induced phrenic nerve activity (PNA) is dependent on RTN, as previously demonstrated (22,24,27), whereas sympathoexcitation and pressor responses are only partially mediated by RTN (24). The reduced sympathoexcitation produced by hypercapnia after injection of the NMDA glutamate antagonist (AP-5) into the RTN, might also be the result of the decrease in the excitability of RVLM presympathetic neurons after removing baseline facilitatory glutamatergic signals from the RTN (Figure 2).…”
Section: The Retrotrapezoid Nucleus Contributes To the Sympathoexcitasupporting
confidence: 71%
See 3 more Smart Citations
“…The results suggest that central chemoreceptor-induced phrenic nerve activity (PNA) is dependent on RTN, as previously demonstrated (22,24,27), whereas sympathoexcitation and pressor responses are only partially mediated by RTN (24). The reduced sympathoexcitation produced by hypercapnia after injection of the NMDA glutamate antagonist (AP-5) into the RTN, might also be the result of the decrease in the excitability of RVLM presympathetic neurons after removing baseline facilitatory glutamatergic signals from the RTN (Figure 2).…”
Section: The Retrotrapezoid Nucleus Contributes To the Sympathoexcitasupporting
confidence: 71%
“…Recently, we have shown that inhibition of the chemosensitive neurons located in the RTN eliminated resting breathing and reduced the sympathoexcitatory responses produced by central chemoreceptor activation (24). The results suggest that central chemoreceptor-induced phrenic nerve activity (PNA) is dependent on RTN, as previously demonstrated (22,24,27), whereas sympathoexcitation and pressor responses are only partially mediated by RTN (24).…”
Section: The Retrotrapezoid Nucleus Contributes To the Sympathoexcitasupporting
confidence: 51%
See 2 more Smart Citations
“…Está bem estabelecido na literatura a contribuição do grupamento C1 durante a ativação dos quimiorreceptores periféricos e centrais, no que diz respeito ao controle autônomo, mais especificamente na modulação da atividade simpática Koshiya, Guyenet, 1996;Moreira et al, 2006;Takakura et al, 2011;Moraes et al, 2013). No entanto, a participação dos neurônios C1 no controle respiratório só foi descoberta recentemente Burke et al, 2014).…”
Section: Grupamento Adrenérgico C1 E O Controle Respiratóriounclassified